To find the 34th term of an arithmetic sequence, we can use the formula:
an = a1 + (n-1)d
Where:
an = the nth term
a1 = the first term
n = the term number
d = the common difference
In this case:
a1 = 97
d = -6 (since each term decreases by 6)
n = 34
Plugging into the formula:
a34 = 97 + (34-1)(-6)
a34 = 97 + 33(-6)
a34 = 97 - 198
a34 = -101
So, the 34th term of the arithmetic sequence 97, 91, 85, ... is -101.
Determine the 34th term of the arithmetic sequence 97, 91, 85, . . . .(1 point)
1 answer